Validation of cardiac magnetic-resonance-derived left ventricular strain measurements from free-breathing motion-corrected cine imaging. - Merlocco, Anthony; Cross, Russell R.; Kellman, Peter; Xue, Hui; Olivieri, Laura (Pediatric Radiology, 2019)
Background: Myocardial strain is an important measure of cardiac function and can be assessed on cardiac magnetic resonance (MR) through the current gold standard of breath-held segmented steady-state free precession (SSFP) cine imaging. Novel free-breathing techniques have been validated for volumetry and systolic function, allowing for evaluation of sicker and younger children who cannot reliably hold their breath. It is unclear whether strain measurements can be reliably performed on free-breathing, motion-corrected, re-binning cine images.Objective: To compare strain analysis from motion-corrected retrospective re-binning images to the breath-held SSFP cine images to explore their validity.Materials and Methods: Twenty-five children and young adults, ages (2.1-18.6 years) underwent breath-held and motion-corrected retrospective re-binning cine techniques during the same MR examination on a 1.5-tesla magnet. We measured endocardial end-systolic global circumferential strain and endocardial averaged segmental strain using commercial software (MEDIS QStrain 2.1). We used Pearson correlation coefficients to test agreement across techniques.Results: Analysis was possible in all 25 breath-held and motion-corrected retrospective re-binning studies. Global circumferential strain and endocardial averaged segmental strain obtained by motion-corrected retrospective re-binning compared favorably to breath-held studies. Global circumferential strain linear regression models demonstrated acceptable agreement, with coefficients of determination of 0.75 for breath-held compared to motion-corrected retrospective re-binning (P<0.001) and for endocardial averaged segmental strain comparisons yielded 0.77 for breath-held vs. motion-corrected retrospective re-binning (P<0.001). Bland-Altman assessment demonstrated minimal bias for breath-held compared to motion-corrected retrospective re-binning (mean 2.4 and 1.9, respectively, for global circumferential strain and endocardial averaged segmental strain).Conclusion: Free-breathing imaging by motion-corrected retrospective re-binning cine imaging provides adequate spatial and temporal resolution to measure myocardial deformation when compared to the gold-standard breath-held SSFP cine imaging in children with normal or borderline systolic function.